Hydrotalcites Promoted by NaAlO2 as Strongly Basic Catalysts with Record Activity in Glycerol Carbonate Synthesis. Issue 6 (12th February 2018) - Ramesh, Sreerangappa; Devred, François; van den Biggelaar, Ludivine; Debecker, Damien P.
Abstract: A new type of highly basic catalysts is obtained by promoting Mg–Al layered double hydroxides with sodium aluminate. The Mg–Al mixed oxides obtained by the calcination of pristine hydrotalcites are poorly active in the synthesis of glycerol carbonate from glycerol and dimethyl carbonate (DCM). Pure sodium aluminate on the other hand is highly active in this reaction, but it is also highly corrosive, making its handling problematic. Remarkably, promoting hydrotalcites with low amounts of sodium aluminate is sufficient to reach high yields. At 90 °C, with 3 wt % catalyst and with a DMC/glycerol ratio of 2:1, a glycerol conversion of 92 % was achieved after 30 min over the 10 wt % NaAlO2 /hydrotalcite catalyst with almost 100 % selectivity towards glycerol carbonate. The texture and the crystallinity of the catalysts were strongly affected by the addition of NaAlO2 . The high activity was clearly correlated with the boost in basicity brought about by sodium aluminate promotion. Whereas pristine hydrotalcites possess only weak basic sites, the basicity of the catalysts increased drastically upon promotion with NaAlO2, both in amount and strength. Diffuse reflectance infrared spectroscopy coupled with CO2 adsorption measurements revealed the presence of surface carbonates arising from strongly basic sites. Importantly, our study demonstrates that these basic catalysts are truly heterogeneous, stable, and reusable. Abstract : Catalyst upgrade : Hydrotalcites are well‐known basic catalysts but perform poorly in the synthesis of glycerol carbonate. NaAlO2 is highly active but not convenient. Promoting hydrotalcites with low amounts of sodium aluminate leads to excellent catalysts that combine the benefits of the two partners.